Accessibility of care plan information from previous treatment setting in palliative care unit: A qualitative study - Kuusisto Anne; Saranto Kaija; Korhonen Päivi; Haavisto Elina (WILEY, 2022)
Aim: To describe accessibility of care plan information from patients' previous treatment setting in palliative care.
Design: A qualitative descriptive study.
Methods: A total of 33 nurses, social workers and physicians were interviewed. Data were analysed by deductive and inductive content analysis. The Fit between Individuals, Task and Technology (FITT) framework was used as a deductive analysis framework.
Results: Individual-task Fit was described in relation to professional-specific care plan information in palliative care and use of time to obtain care plan information. Individual-technology Fit was described in relation to health informatics competencies and HIS usability. Task-technology Fit was described in relation to interoperability between care settings and healthcare providers and lack of interoperability between care settings and healthcare providers.
Relevance to clinical practice: The study confirms the need to review the HIS as a whole from a holistic and patient-oriented perspective to ensure the continuity of palliative care.